Integrating Electronic Portfolio Assessment into Teaching Materials: An Exploratory Study on Speaking Course Syllabus Development - Moh. Taufik; Sari Karmina; Bambang Yudi Cahyono; Tengku Intan Suzila bt Tengku Sharif; Nur Mukminatien; Suharyadi Suharyadi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: The ICT advancement provokes the possibility of developing speaking skill through portfolio assessment which was commonly attributable mostly to writing skill. Hence, an exploratory study adopting ADDIE model was conducted to develop an electronic portfolio assessment integrated into teaching materials. A triangulated technique of data collection: questionnaire respondents, interviews and data from evaluation sheets was gathered. Statistical descriptive analysis, discourse and content analysis were conducted and positive possibilities were found to ffacilitate the development of speaking skills through electronic portfolio assessment.